Carbon Monoxide Poisoning at a Swface Coal Mine . . . . A Case Study - Kenneth Eltschlager; William Shuss; Thomas Kovalchuk (International Society of Explosives Engineers, 2001)
In April of 2000, two adults and their newborn infant, were poisoned by carbon monoxide in their home and received medical treatment at a Pennsylvania hospital. Carboxyhemoglobin levels were; child - 3 1%, father - 28Oh, and mother - 17%. Initially the furnace was blamed but after further review, blasting at a nearby coal mine was determined to be the source. All other sources of carbon monoxide were ruled out. The blasting was about 400 feet from the house. The conditions that led to the migration of gas include: the blasts were highly confined, the geologic structure contained fractures that served as conduits for the carbon monoxide to reach a hand-dug well outside the house, and the well was atmospherically connected to the basement floor drains.